Oral Vancomycin, Ursodeoxycholic Acid, or No Therapy for Pediatric Primary Sclerosing Cholangitis: A Matched Analysis. Issue 3 (17th March 2021) - Deneau, Mark R.; Mack, Cara; Mogul, Douglas; Perito, Emily R.; Valentino, Pamela L.; Amir, Achiya Z.; DiGuglielmo, Matthew; Draijer, Laura G.; El‐Matary, Wael; Furuya, Katryn N.; Gupta, Nitika; Hochberg, Jessica T.; et al.
Abstract : Background and Aims: Many children with primary sclerosing cholangitis (PSC) receive oral vancomycin therapy (OVT) or ursodeoxycholic acid (UDCA). There is a paucity of data on whether these medications improve outcomes. Approach and Results: We analyzed retrospective data from the Pediatric PSC Consortium. Children treated with OVT were matched 1:1:1 to those treated with UDCA or managed with observation (no treatment) based on the closest propensity score, ensuring similar baseline characteristics. Two hundred sixty‐four patients (88 each with OVT, UDCA, or observation) had matching propensity scores and were similar in demographics, phenotype, immunosuppression, baseline biochemistry, and hepatic fibrosis. After 1 year in an intention‐to‐treat analysis, all outcome metrics were similar regardless of treatment group. In OVT, UDCA, and untreated groups, respectively: Gamma‐glutamyltransferase normalized in 53%, 49%, and 52% ( P = not significant [NS]), liver fibrosis stage was improved in 20%, 13%, and 18% and worsened in 11%, 29%, and 18% ( P = NS), and the 5‐year probability of liver transplant listing was 21%, 10%, and 12% ( P = NS). Favorable outcome was associated with having a mild phenotype of PSC and minimal hepatic fibrosis. Conclusions: We presented the largest‐ever description of outcomes on OVT in PSC and compared them to carefully matched patients on UDCA or no therapy. Neither OVT nor UDCA showed improvement in outcomes compared to a strategy of observation. Patients progressed to end‐stage liver disease at similar rates. Spontaneous normalization of biochemistry is common in children receiving no therapy, particularly in the majority of children with a mild phenotype and an early stage of disease. Placebo‐controlled treatment trials are needed to identify effective treatments for pediatric PSC.